THE EFFECT OF WORK DISCIPLINE AND KNOWLEDGE SHARING ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE AT PETROLEUM AND GAS COMPANIES IN INDONESIA - Anggraini, Resty; Susita, Prof. Dr. Dewi; Wiradendi, Dr. Christian (jfpublisher, 2023)
Pertamina is committed to improve the quality of its human resources, which is important for the company's business. The company is managed by a professional leadership and structure of workers, which is the result of the implementation of a structurally planned human resource development system and program. Therefore, the objective of this research is to find out the effect of work discipline and knowledge sharing on employee performance with work discipline as a mediator. This research uses quantitative methods and is conducted through structural equation modeling analysis with AMOS. The respondents involved in this research were employees of PT Pertamina Patra Niaga located at the central office, with a sample of 355 employees selected through the propotioned sampling method. The results indicated that work discipline, knowledge sharing, and work motivation have a positive effect on employee performance. In addition, work discipline and knowledge sharing have a positive effect on work motivation. Unfortunately, work motivation is not able to mediate the indirect effect between work discipline and knowledge sharing on employee performance.